2019
DOI: 10.1039/c8sm02374c
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical investigation into the antibacterial action of modelin-5-NH2

Abstract: Neutron diffraction studies showed that modelin-5-CONH2has potent antibacterial activity which involves membrane interactive, tilted α-helical structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(29 citation statements)
references
References 58 publications
(108 reference statements)
4
25
0
Order By: Relevance
“…Analysis of these spectra showed that the α-helicity of these peptides was lower than in the case of a TFE and PBS (10 mM, 3) and ranged between 48.9 % and 66.6% for SUVs formed from DMPG (Table 4, Figure 6A), and between 34.3 % and 47.9 % for those formed from DMPE (Table 4, Figure 6B). These levels of α-helical structure are consistent with previous reports [27] and generally comparable to those adopted by other aureins [63,67,68]. Aurein 2.1, aurein 2.6 and aurein 3.1 induced maximal surface pressures in monolayers formed from DMPG that varied between π = 9.8 mN m -1 and π = 12.0 mN m -1 , and between π = 7.7 mN m -1 and π = 8.5 mN m -1 in those formed from DMPE (Table 4, Figure 7).…”
Section: Properties Of Aureins and Their Pegylated Isoforms At A Memb...supporting
confidence: 92%
See 1 more Smart Citation
“…Analysis of these spectra showed that the α-helicity of these peptides was lower than in the case of a TFE and PBS (10 mM, 3) and ranged between 48.9 % and 66.6% for SUVs formed from DMPG (Table 4, Figure 6A), and between 34.3 % and 47.9 % for those formed from DMPE (Table 4, Figure 6B). These levels of α-helical structure are consistent with previous reports [27] and generally comparable to those adopted by other aureins [63,67,68]. Aurein 2.1, aurein 2.6 and aurein 3.1 induced maximal surface pressures in monolayers formed from DMPG that varied between π = 9.8 mN m -1 and π = 12.0 mN m -1 , and between π = 7.7 mN m -1 and π = 8.5 mN m -1 in those formed from DMPE (Table 4, Figure 7).…”
Section: Properties Of Aureins and Their Pegylated Isoforms At A Memb...supporting
confidence: 92%
“…These peptides also induced levels of lysis that varied between 59.6% and 71.3% in the case of SUVs formed from DMPG and between 31.7% and 40.6% in the case of those formed from DMPE (Table 4). Comparable levels of membrane interaction have been shown for other aureins and HDPs [68][69][70] and in combination, these data show that the aureins studied here adopted high levels of lipid interactive, α-helical structure (Table 4, Figure 6) and have a strong propensity to penetrate and lyse both anionic and zwitterionic lipid membranes (Table 4, Figure 7). These observations clearly suggested that this propensity is driven by the strongly amphiphilic nature of the α-helical structure formed by these peptides and similar structure / function relationships underpin the membranolytic mechanisms of most α-helical HDPs [7,20,66].…”
Section: Properties Of Aureins and Their Pegylated Isoforms At A Memb...supporting
confidence: 67%
“…26,66 The capacity for potent membranolytic activity appears to generally underpin the antibacterial activity of M5-NH 2 , which suggested that changes to this capacity may be involved in the resistance of S. aureus to the peptide's action. 26,31,33,66 Consistent with this suggestion, M5-NH 2 displayed low levels of binding to SUVs mimetic of the S. aureus CM ( K d = 117.6 μM) that were over five times lower than in the case of P. aeruginosa , reflecting the peptide's weaker activity against the former organism (Table 2). The peptide also adopted low levels of amphiphilic α-helical structure in the presence of these SUVs (Fig.…”
Section: Resultssupporting
confidence: 59%
“…31,33,66 Amphiphilic profiling has shown that M5-NH 2 exhibits high levels of amphiphilicity along the length of its α-helical conformation 33 and it has been demonstrated that this structural property drives major steps in its membranolytic action against other bacteria. 31,33,66…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation